2019
DOI: 10.1016/j.jpeds.2019.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Day-Night Activity in Hospitalized Children after Major Surgery: An Analysis of 2271 Hospital Days

Abstract: Objectives: To characterize the day-night activity patterns of children after major surgery and describe differences in children's activity patterns between the PICU and inpatient floor setting. Study design: In this prospective observational study, we characterized the daytime activity ratio estimate (DARE; ratio between mean daytime activity [08:00-20:00] and mean 24-h activity [00:00-24:00]) for children admitted to the hospital after major surgery. The study sample included 221 infants and children ages 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…The Actical movement monitor (Respironics, Inc.) is a small, non-invasive, wristwatch-sized device that contains an omnidirectional accelerometer designed to measure physical activity and caloric expenditure on a continuous basis. The movement monitor provides an objective, quantifiable measure of physical movement and has been used in past studies of children in a post-surgical hospital setting (Kudchadkar et al, 2019;Puyau, Adolph, Vohra, Zakeri, & Butte, 2004). The movement monitor was placed on the child's wrist when they arrived in the post-operative care unit after surgery and left in place until they were discharged.…”
Section: Actigraphymentioning
confidence: 99%
“…The Actical movement monitor (Respironics, Inc.) is a small, non-invasive, wristwatch-sized device that contains an omnidirectional accelerometer designed to measure physical activity and caloric expenditure on a continuous basis. The movement monitor provides an objective, quantifiable measure of physical movement and has been used in past studies of children in a post-surgical hospital setting (Kudchadkar et al, 2019;Puyau, Adolph, Vohra, Zakeri, & Butte, 2004). The movement monitor was placed on the child's wrist when they arrived in the post-operative care unit after surgery and left in place until they were discharged.…”
Section: Actigraphymentioning
confidence: 99%
“…Many studies from this group analyze patient dissatisfaction, as well as factors that influence their risk level [6][7][8][9]. These studies are significantly heterogenous in their character.…”
Section: Overview Of the Research Studiesmentioning
confidence: 99%
“…Experience in performing day surgery in many countries points to the necessity of its own administrative infrastructure in order to ensure coordinated planning and continuity in the performance of day surgery as well as overall optimization. Many foreign studies (e.g., [17,[21][22][23][24][25][26][27][28], and others) have declared an effort to continually expand the day surgery system, both the number of patients operated and the application of more extensive and complex procedures (e.g., [7][8][9]) in patients with higher rates of comorbidity. This creates the preconditions for a more in-depth examination of regional disparities in the development of the number of surgeries performed and the factors that cause them.…”
Section: Overview Of the Research Studiesmentioning
confidence: 99%
“…It has been proven in several studies that children will feel safe when they are beside their parents, especially when facing invasive procedure (Supartini, 2004). Casey in (Supartini, 2004)suggested that the principle of nursing services to children must focus on children and families, to meet the needs of children and their families (Kudchadkar et al, 2019;Moghaddam et al, 2017). The purpose of this study is to analyze the effect of family support systems on coping mechanisms of preschool children.…”
Section: Introductionmentioning
confidence: 99%